2018
DOI: 10.5194/acp-2018-1018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling the microphysics of polar mesospheric cloud formation

Abstract: <p><strong>Abstract.</strong> Polar mesospheric clouds are the highest water ice clouds occurring in the terrestrial atmosphere. They form in the polar summer mesopause, the coldest region in the atmosphere. It has long been assumed that these clouds form by heterogeneous nucleation on meteoric smoke particles which are the remnants of material ablated from meteoroids in the upper atmosphere. However, until now little was known about the properties of these nm-size par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 42 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…We found that the primary ice phase forming on the MSP analogues at the conditions of the summer mesopause is Amorphous Solid Water (ASW) (Nachbar et al, 2018b;Nachbar et al, 2018c). Additionally, we showed that MSPs adsorb up to several layers of water until ice growth activates as soon as the saturation exceeds the saturation vapor pressure of ASW including the Kelvin effect for the ice-covered or "wet" particle radius, and considering the collision radius of water molecules (Duft et al, 2018). Asmus et al (2014) pointed out that MSPs may heat up in the low density atmosphere of the mesopause by absorbing solar and terrestrial irradiation.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…We found that the primary ice phase forming on the MSP analogues at the conditions of the summer mesopause is Amorphous Solid Water (ASW) (Nachbar et al, 2018b;Nachbar et al, 2018c). Additionally, we showed that MSPs adsorb up to several layers of water until ice growth activates as soon as the saturation exceeds the saturation vapor pressure of ASW including the Kelvin effect for the ice-covered or "wet" particle radius, and considering the collision radius of water molecules (Duft et al, 2018). Asmus et al (2014) pointed out that MSPs may heat up in the low density atmosphere of the mesopause by absorbing solar and terrestrial irradiation.…”
Section: Introductionmentioning
confidence: 94%
“…In this section we discuss the impact of solar radiation on the critical temperature of the environment T cr,env needed to activate ice growth. To this end we combine our previously presented ice growth activation model (Duft et al, 2018) with the equilibrium temperature model of this work. A description of the method can be found in Appendices A and B.…”
Section: The Impact Of Solar Radiation On Ice Particle Formation 10mentioning
confidence: 99%
See 3 more Smart Citations